Analysis of the impact of unforced errors in tennis - Peiris, H.; Epasinghege Dona, N.; Swartz, T. B. (International Journal of Sports Science & Coaching, 2025)
This paper investigates unforced errors in tennis which is facilitated by a rich dataset. Descriptive analyses are carried out which studies the distribution of unforced error rates across professional tennis players, the identification of players with high and low rates, the relationship between rates and match winning percentage, the relationship between rates and aggressiveness (via hitting winners), the relationship between rates and touch number, and the study of rates versus time. Methods are then developed to assess the impact of unforced errors which are applicable to any racquet sport. We demonstrate the approach in the context of professional tennis with an investigation of the longstanding rivalry between Roger Federer and Rafael Nadal. The value of the approach is that we can provide estimates of the points lost, games lost, sets lost and matches lost due to unforced errors. The methods are based on a bootstrapping procedure which also yields standard errors for the estimates. The approach is valuable in terms of player evaluation, and can also be used for training purposes where it is possible to assess the quantification of improvement based on fewer unforced errors.